The seasonal effect on the performance of pigs reared in a backyard pig farm in Thailand: retrospective study - M. Lothong; K. Anurud; S. Semsirmboon; S. Poonyachoti; S. Thammachareon (Journal of the Indonesian Tropical Animal Agriculture, 2022)
This study aimed to determine the seasonal effect on the performance of pigs reared in open-barn housing in Thailand. This retrospective study was performed using two years of recorded pig perfor-mance, including average birth weight, litter size, percentage of born alive and dead piglets, weaning weight, average daily gain (ADG), percentage of weaned alive and dead piglets and meteorological data. Data were grouped based on 3 different seasons: winter, summer and the rainy season, and the differences were compared. The highest temperature–humidity index (THI) was found during summer (85.3 ± 0.2) and the THI of the rainy season was higher than that in winter (between 82.3 ± 0.2 and 77.2 ± 0.4) (p < 0.05). The piglet growth performance was affected by season (p < 0.05). The weaning weight of piglets in the rainy season was higher than that in winter but not different from that in sum-mer. The highest ADG was observed in the rainy season. In summary, growth performance of suckling pigs reared in open-barn housing in Thailand was affected by the season. The optimal climate promot-ing growth of nursery pigs was determined to be the rainy season.